Human experimental pain models - Mastilović, Gligor; Konstantinovic, Uros; Djordjevic, Olivera (Medicinski podmladak, 2020)
Pain is unpleasant sensory experience, associated with existing or potential tissue damage. It also has strong cognitive and emotional components. Stimuli which causes pain goes through process of nociception which includes transduction, transmission, modulation and perception of said stimuli. Depending on the type of stimuli, we can classify human experimental pain models into mechanical, electrical, thermal and chemical. Information about pain mechanisms can be obtained from: 1) in vitro studies, 2) animal experiments, 3) human experimental pain studies, and 4) clinical studies. Chosing the appropriate method for pain evaluation is a key step in design of pain studies. Combining it with different electro-physiological and imaging methods can provide us with better objectivity and quantification of pain mechanisms. Focus in experimental pain studies is slowly shifting from static parameters of pain such as pain treshold and maximum tolerance to dynamic parameters which can give us valuable insight in function of endogenous analgesic systems. This can be done using conditioned pain modulation. Using experimental pain on healthy voulenteers is key step in switching from animal models to clinical studies, foremost for validization of data from animals, making them important in translational research. Results from experimental pain studies can help us in understanding nociceptive mechanisms of acute and chronic pain as well as with development of new therapeutic modalities.